Adenosine regulates bone metabolism via A(1), A(2A), and A(2B) receptors in bone marrow cells from normal humans and patients with multiple myeloma - He, Wenjie (Federation of American Societies for Experimental Biology, 2013)
Multiple myeloma (MM) is characterized by osteolytic bone lesions with uncoupled bone remodeling. In this study, we examined the effects of adenosine and its receptors (A(1)R, A(2A)R, A(2B)R, and A(3)R) on osteoblast and osteoclast differentiation of cells derived from patients with MM and healthy control subjects. Mesenchymal stem cells and bone marrow-derived mononuclear cells were isolated from bone marrow and differentiated into osteoblasts and osteoclasts, respectively. A(1)R antagonist rolofylline and A(2B)R agonist BAY60-6583 inhibit osteoclast differentiation of cells from patients with MM in a dose-dependent manner, as shown by TRAP staining (IC(50): 10 and ∼10 nM, respectively). BAY60-6583 and dipyridamole, a nucleoside transport inhibitor, stimulate osteoblast differentiation of cells from patients with MM, as measured by ALP activity at d 14 and Alizarin Red staining at d 21 (by 1.57±0.03- and 1.71±0.45-fold, respectively), which can be blocked by A(2B)R antagonist MRS1754. Consistently, real-time PCR showed a significant increase of mRNA of osteocalcin and osterix at d 14. The effect of adenosine and its receptors is consistent in patients with MM and healthy subjects, suggesting an intrinsic mechanism that is important in both MM bone metabolism and normal physiology. Furthermore, the effect of dipyridamole on osteoblast differentiation is diminished in both A(2B)R- and CD39-knockout mice. These results indicate that adenosine receptors may be useful targets for the treatment of MM-induced bone disease.—He, W., Mazumder, A., Wilder, T., Cronstein. B. N. Adenosine regulates bone metabolism via A(1), A(2A), and A(2B) receptors in bone marrow cells from normal humans and patients with multiple myeloma.